The EU's Rule of Law Promotion in Central and Eastern Europe: Where and Why Does It Fail, and What Can Be Done About It? - Martin Mendelski (Bingham Centre for the Rule of Law, 2016)
This policy paper identifies two key dilemmas of the EU's rule of law promotion: 1. The problem of supporting unaccountable reformers in a partisan way (ownership dilemma); 2. The problem of valuing quantity over quality (change vs. stability dilemma). It is argued that these dilemmas reinforce legal pathologies which undermine the rule of law in Central and Eastern Europe. The paper offers two unconventional policy recommendations to enhance the quality of rule of law reform and assessment.
Keywords: 330; Central and Eastern Europe; European Union; Europeanization; rule of law